Advances in surface modification of tantalum and porous tantalum for rapid osseointegration: A thematic review - Wang, Xi; Liu, Wentao; Yu, Xinding; Wang, Biyao; Xu, Yan; Yan, Xu; Zhang, Xinwen (Frontiers in Bioengineering and Biotechnology, 2022)
After bone defects reach a certain size, the body can no longer repair them. Tantalum, including its porous form, has attracted increasing attention due to good bioactivity, biocompatibility, and biomechanical properties. After a metal material is implanted into the body as a medical intervention, a series of interactions occurs between the material’s surface and the microenvironment. The interaction between cells and the surface of the implant mainly depends on the surface morphology and chemical composition of the implant’s surface. In this context, appropriate modification of the surface of tantalum can guide the biological behavior of cells, promote the potential of materials, and facilitate bone integration. Substantial progress has been made in tantalum surface modification technologies, especially nano-modification technology. This paper systematically reviews the progress in research on tantalum surface modification over the last 10 years for the first time, including physicochemical properties, biological properties, and surface modification technologies of tantalum and porous tantalum.